Pengembangan Kurikulum Berbasis Nilai Moral Dalam Meningkatkan Pendidikan Karakter Siswa Sekolah Dasar - Sofia Nur Kartika; Ramadona Ramadona; Linafatul Khofifah; Endang Fauziati; Bambang Sumardjoko (Mathematics Education Study Program, 2025)
Character education is the main foundation in building a young generation with integrity and responsibility. This research uses case study research with a descriptive qualitative approach. This research aims to develop a moral values-based curriculum to improve student character education in elementary schools. Even though character education is considered important, challenges in its implementation often arise, such as a lack of integration of moral values ​​in the existing curriculum and low student awareness of the importance of morals and ethics. By developing a curriculum that includes learning objectives, materials, methods and evaluation that are integrated with character values, it is hoped that it can instill a positive personality and encourage students to socialize and be responsible. The research results show that the implementation of a moral values-based curriculum not only increases students' honest and disciplined attitudes, but also increases their participation in learning. Thus, character education must be an integral part of the curriculum to create a young generation who is not only academically intelligent but also has good morals.